Genome Editing with mRNA Encoding ZFN, TALEN, and Cas9 - Zhang, Hong-Xia; Zhang, Ying; Yin, Hao (Molecular therapy, 2019)
Genome-editing technologies based on programmable nucleases have significantly broadened our ability to make precise and direct changes in the genomic DNA of various species, including human cells. Delivery of programmable nucleases into the target tissue or cell is one of the pressing challenges in transforming the technology into medicine. In vitro-transcribed (IVT) mRNA-mediated delivery of nucleases has several advantages, such as transient expression with efficient in vivo and in vitro delivery, no genomic integration, a potentially low off-target rate, and high editing efficiency. This review focuses on key barriers related to IVT mRNA delivery, on developed modes of delivery, and on the application and future prospects of mRNA encoding nuclease-mediated genome editing in research and clinical trials. In vitro-transcribed (IVT) mRNA mediates the delivery of genome-editing nucleases. Zhang et al. review key barriers related to IVT mRNA delivery, developed modes of delivery, and the application and future prospects of mRNA encoding nuclease-mediated genome editing in research and clinical trials.